Stent Placement in Surgically Altered Stomach - Tsauo, Jiaywei; Park, Jung-Hoon; Zhang, Xiaowu; Zhao, He; Song, Ho-Young (Digestive Disease Interventions, 2018)
Gastric cancer is one of the most common malignancies and among the leading causes of cancer-related deaths worldwide. Radical gastrectomy has been the mainstay of curative treatment for gastric cancer, but recurrent cancer occurs in a significant number of patients. Patients with recurrent cancer can experience debilitating symptoms due to malignant gastric outlet obstruction (GOO). Self-expandable metallic stent (SEMS) placement is effective and safe for the palliative treatment of malignant GOO. However, the technical difficulty of SEMS placement is higher in patients with recurrent cancer due to the surgically altered stomach. Thorough understanding of the surgically altered anatomy and site of stricture is key to favorable treatment outcomes.
Keywords: stomach neoplasms; gastrectomy; gastric outlet obstruction